2014
DOI: 10.5551/jat.25536
|View full text |Cite
|
Sign up to set email alerts
|

An Overweight or Obese Status in Childhood Predicts Subclinical Atherosclerosis and Prehypertension/Hypertension in Young Adults

Abstract: Aim:The aim of this study, the YOung TAiwanese Cohort (YOTA) Study, was to investigate the relationship between a childhood overweight/obese status and young adult preclinical atherosclerosis, including assessments of the carotid intima-media thickness (CIMT) and prehypertension or hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
(38 reference statements)
0
25
0
1
Order By: Relevance
“…The measurements of PFAS have been validated (Lin et al, 2013b) and have been demonstrated to have different health effects in this cohort (Lin et al, 2011(Lin et al, , 2013aSu et al, 2014). This study also had several limitations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The measurements of PFAS have been validated (Lin et al, 2013b) and have been demonstrated to have different health effects in this cohort (Lin et al, 2011(Lin et al, , 2013aSu et al, 2014). This study also had several limitations.…”
Section: Discussionmentioning
confidence: 94%
“…Trained assistants and nurses invited these subjects by mail or/and telephone to undergo the health examination and complete a questionnaire. The information has been detailed in previous studies (Lin et al, 2013a,b;Su et al, 2014). Out of 7097 subjects living in Taipei, 790 students completed the follow-up health examination, including the collection of a blood sample and the completion of a questionnaire, but we did not measure the serum PFAS or reproductive hormone levels of all of the subjects due to the collection of limited serum samples.…”
Section: Subjects and Data Collectionmentioning
confidence: 99%
“…The CIMT is correlated with coronary and carotid atherosclerosis and is a significant predictor of future cardiovascular events. Thus, CIMT has been widely used in many clinical studies as a surrogate marker of coronary and carotid atherosclerosis and the risk of cardiovascular diseases [11][12][13][14][15] .…”
Section: Reagents and Laboratory Measurementsmentioning
confidence: 99%
“…Obesity is closely associated with atherogenic dyslipidemia, and metabolic syndrome is a significant risk factor contributing to the development of atherosclerosis 1) . Childhood obesity also reported to be significantly related to the hypertension and the thicker carotid intima-media thickness (IMT) in young Asian adults 2) . In addition, from the point that the number of adipocytes is set during childhood and adolescence 3) , medical experts should try to prevent obesity in children.…”
Section: Introductionmentioning
confidence: 99%